Ovarian follicle dynamics in the plains zebra (Equus quagga) - Lawrence O. Barros; Kendall A. Hyde; Nathalie Gazzaniga; Melba O. Gastal; Francisco L. N. Aguiar; Gustavo F. Carneiro; Eduardo L. Gastal (PLoS ONE, 2026)
Understanding follicular dynamics during the estrous cycle is essential for developing breeding programs and assisted reproductive technologies (ARTs) in any species. In this context, knowledge of follicular dynamics and related uterine changes in the plains zebra ( Equus quagga ) is essential to increase the declining population of this vital African species and to provide comparative insights into more endangered zebra species. Likely due to the difficulty of handling these wild species, no detailed reproductive study using ultrasonography has been performed in any zebra. Therefore, the present study aimed to describe follicular dynamics and endometrial echotexture changes in plains zebras using data collected daily via transrectal ultrasonographic monitoring of the ovaries and uterus during spontaneous estrous cycles (no exogenous hormones administered; Experiment 1) and induced ovulatory periods (exogenous hormones administered; Experiment 2). Data from four plains zebra mares revealed that their spontaneous estrous cycles (n = 9) are characterized by a long interovulatory interval (IOI; approximately 38 days), low daily antral follicle count during the IOI (approximately 3 follicles), an absence of follicular waves, a slow follicular growth rate (approximately 1 mm per day), and a relatively similar mean ovulatory follicle diameter (approximately 36 mm) compared to domestic equids. Furthermore, the zebra shows endometrial echotexture patterns similar to those of the horse mare during the preovulatory period. Additionally, by evaluating induced ovulatory periods in two zebras (n = 10 periods), it was shown that these animals respond reliably to luteolytic and ovulation synchronization drugs. Overall, the information provided in this study is vital for the development of breeding programs and ARTs in the plains zebra. In this way, conservation efforts can not only begin to improve the numbers of the plains zebra but also use the information learned from this species to inform efforts for other, more endangered zebras.